Activation of protective cell-mediated immune response in gastric mucosa during Cryptosporidium muris infection and re-infection in immunocompetent mice - Jalovecká, Marie; Sak, Bohumil; Kvác, Martin; Kvetonová, Dana; Kucerová, Zuzana; Salát, Jirí (Parasitology research, 2010)
Gastric cryptosporidia only inhabit the glandular part of the stomach of all age categories of their hosts and can cause chronic life-long infections independent of a host's immune status. The immune response in the stomach mucosa during the primary infection and re-infection with Cryptosporidium muris (TS03 and CB03) in immunocompetent BALB/c mice was characterized using flow cytometry analysis and measurement of IFN-gamma and IL10 by enzyme-linked immunosorbent assays (ELISA). Significantly, elevated migration of T lymphocytes (more than 1,000-fold), especially CD8+ T lymphocytes, to the stomach mucosa occurred during primary infection and persisted for more than 2 months after its resolution. The ex vivo cultures of splenocytes revealed very low levels of IFN-gamma production during the course of the primary infection (0.5 ng/ml), whereas in the following re-exposure to the parasites, the concentration of IFN-gamma rapidly increased 22-fold. Although the two parasite strains that were tested were genetically distinct, they yielded similar results in the induction of cellular immune responses, suggesting that these patterns are not unique to a single parasite strain. These results imply that the CD8+ T lymphocytes are involved in the immune response to gastric cryptosporidiosis and could play an important role in the elimination of C. muris infection in mice.
Keywords: žaludeční sliznice; Gastric Mucosa; T-Lymphocyte Subsets; Interferon-gamma; slezina; kryptosporidióza; interleukin-10; Cryptosporidiosis; myši inbrední BALB C; interferon gama; Interleukin-10; T-lymfocyty - podskupiny; Flow Cytometry; ELISA; Mice, Inbred BALB C; Spleen; Enzyme-Linked Immunosorbent Assay; průtoková cytometrie; Animals; lidé; buněčná imunita; ženské pohlaví; Humans; zvířata; Immunity, Cellular; myši; Cryptosporidium; Immunity, Mucosal; Mice; Female; slizniční imunita